2002
DOI: 10.1007/s00432-002-0346-1
|View full text |Cite
|
Sign up to set email alerts
|

Human hormone-refractory prostate cancers can harbor mutations in the O 2 -dependent degradation domain of hypoxia inducible factor-1α (HIF-1α)

Abstract: Some human hormone-refractory prostate cancers have mutations in a critical regulatory domain of the HIF-1alpha protein. We believe that these mutations might enable expression of this protein under inappropriate conditions and contribute to the development of therapeutic resistance by the cancer cells. This hypothesis is currently being tested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 16 publications
0
23
0
Order By: Relevance
“…The identification of mutations within the oxygen-dependent domain of HIF-1a was recently shown in a small number of prostate cancers (23,24). The presence of mutations implies that the activation of HIF-1a can be selected for enabling the expression of this protein under inappropriate conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The identification of mutations within the oxygen-dependent domain of HIF-1a was recently shown in a small number of prostate cancers (23,24). The presence of mutations implies that the activation of HIF-1a can be selected for enabling the expression of this protein under inappropriate conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The current study confirms the expression of HIF-1a in prostate cancer and is the first to show the presence of HIF-2a expression. Furthermore, expression of both HIF-1a and HIF-2a were significantly correlated in neoplastic tissues, suggesting that both isoforms play a functional role in the tumor response to hypoxia and therefore play an important role in the development and progression of this disease.The identification of mutations within the oxygen-dependent domain of HIF-1a was recently shown in a small number of prostate cancers (23,24). The presence of mutations implies that the activation of HIF-1a can be selected for enabling the expression of this protein under inappropriate conditions.…”
mentioning
confidence: 99%
“…The lack of significant associations of the HIF-1a P582S polymorphism with aggressive prostate cancer in our study is somewhat at odds given previous observations. We detected a somatic P582S mutation in an androgen-independent prostate cancer case with metastasis to the bone [13] as did another group in prostate tumor [14]. A case-control study observed higher frequencies of the P582S T-containing variant genotypes among 196 androgen-independent prostate cancer cases compared with 196 controls [15].…”
Section: Discussionmentioning
confidence: 51%
“…Interestingly, our group recently identified the P582S C!T as a somatic mutation in bone marrow metastatic biopsies from men with androgen-independent prostate cancers; and our in vitro experiment demonstrated that, under normoxic conditions, this mutation had significantly higher transcription activity, which reflected increased HIF-1a protein expression [13]. Another group also found the same somatic mutation in prostate tumors [14]. One clinical case-control study found that the P582S T-containing variant genotypes were more common among men with androgen-independent prostate cancer [15].…”
Section: Introductionmentioning
confidence: 53%
“…44 However, the P582S polymorphism has been found to be associated with other disease phenotypes, including decreased coronary artery collateralization in ischemic heart disease patients, lower exercise-induced oxygen consumption in patients age 60 and older, prostate carcinoma, head and neck cancer and type 2 diabetes. [45][46][47][48][49][50] …”
Section: Chuvash Polycythemia and The P582s Polymorphism In Hif-1αmentioning
confidence: 99%